Pathways to Female Job Satisfaction: Quantitative Analysis of Influencing Factors: Mengungkap Jalan Menuju Kepuasan Kerja Karyawan Wanita: Analisis Kuantitatif Faktor-Faktor Pengaruh - Achmad Chadisan Choiron; Rifdah Abadiyah (Academia Open, 2023)
This study aims to investigate the impact of work-family conflict, non-physical work environment, and job stress on job satisfaction among female employees within a ceramic manufacturing organization. Employing a quantitative research design with hypothesis testing, a sample of 100 female employees from PT. Roman Ceramics International was surveyed using reliable and validated Likert-scale questionnaires. The data underwent rigorous statistical analysis, including multiple linear regression, determinant coefficient (R2), partial correlation coefficient, t-test, F-test, and classical assumption tests using SPSS version 18. The findings indicated that work-family conflict, non-physical work environment, and job stress collectively and individually influence employee job satisfaction. Notably, the competency variable emerged as the most influential factor. This research provides valuable insights into the complex dynamics affecting job satisfaction among female employees, offering implications for organizations seeking to enhance employee well-being and overall organizational performance. Highlights: The study explores the factors influencing job satisfaction among female employees, focusing on work-family conflict, non-physical work environment, and job stress. The research adopts a quantitative approach, utilizing multiple linear regression analysis and statistical tools such as t-tests and F-tests to examine the relationships between variables. The findings highlight the significant impact of competency on job satisfaction, emphasizing its crucial role in enhancing the overall well-being and performance of female employees. Keywords: Job satisfaction, Female employees, Work-family conflict, Non-physical work environment, Job stress